Measuring Maintainability of Object Oriented Design (MMOOD) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Measuring maintainability early in the  software development life cycle mainly at design phase is a  landmark of crucial significance to software designers,  developers and quality controllers. Initial Measurement of  object oriented software maintainability, absolutely at  design phase supports designers to increase their designs  before the coding starts. Practitioners and developers  repeatedly advocate that maintainability Measurement  should be planned at design phase of development life  cycle. This paper proposes a Maintainability Measurement  Model that works at design phase of system development  life cycle. Furthermore, statistical test is performed to  justify the correlation of Maintainability with its key  contributors Modifiability and Analyzability. The  developed model has been authenticated using  investigational tryout. In decision, it contains the empirical  authentication of the developed maintainability  measurement model.
Keywords: Maintainability; Object Oriented Metrics; Maintainability Factors; Analyzability; Modifiability; Design Phase; Development life cycle